CMS Innovation Center Health Care Innovation Awards : Evaluation Plan - Sandra H. Berry, Thomas W. Concannon (RAND Corporation, 2013)
ix Summary On November 14, 2011, the Center for Medicare and Medicaid Innovation (CMMI) within the Centers for Medicare & Medicaid Services (CMS) announced the Health Care Innovation Challenge. Through this initiative, CMS planned to award up to $900 million in Health Care Innovation Awards (HCIAs), funded through the Affordable Care Act (ACA), for applicants who proposed compelling new models of service delivery or payment improvements that promise to deliver better health, better health care, and lower costs through improved quality of care for Medicare, Medicaid, and Children’s Health Insurance Program (CHIP) enrollees. CMS was also interested in learning how new models would affect subpopulations of beneficiaries (e.g., those eligible for Medicare and Medicaid and complex patients) who have unique characteristics or health care needs that could be related to poor outcomes. In addition, the initiative sought to identify new models of workforce development and deployment, as well as models that can be rapidly deployed and have the promise of sustainability. This report describes a strategy for evaluating the awardees. It is written for use by the CMS staff who will be engaged in planning the evaluations, by individuals and organizations that will conduct or support evaluation activities, and by awardees who will participate in evaluations by sharing information on HCIA programs and program outcomes. A companion report, The CMS Innovation Center Health Care Innovation Awards Database Report: Information on Awardees and their Populations (Morganti et al., 2013), presents detailed information on each of the awardees.